(untitled) (Economic and Political Thought, 2018)
Culture is one of the social and common results of the process of creating reality. According to Luckmann and Berger theory of social constructionism, it is a state of constant transmission of knowledge and an effect of multiplied reinterpretation of the surroundings. At present, the flow of information is an element constructing culture. Every beam carries a message identified through the prism of language, tradition, values and symbolism. One becomes a consumer of culture taking part in other life-related transactions. The culture of global flows is a phenomenon with no clear source, with no traditionally identified sender. Contemporary forms of communication more and more often push the content of a message to the margin of significance. As a consequence, we observe the effect of culture trivialisation (a phenomenon of infotainment) included in the category of industry: a concept variation introduced by Horkheimer and Adorno in Dialectic of Enlightenment. Industry pushes authors away as it stands in opposition to the vanguard. The products of culture take part in competition and fight for funding. Maintaining artistic independence in mercantile surroundings becomes more and more difficult. Market success is proportionally correlated with the cultural level of brand significance a carrier of a particular message. Anticipating customers’ (consumers’) needs, it is necessary to take into consideration economic factors, however, creating culture, which is the clue of the whole process. In case of public patronage, funding culture, the state implements its own objectives, often those of a given political party. It should be taken into consideration that culture is the most stable unifying force and it is most difficult to change it. It is not possible to leave a culture family as a result of a single political decision. Level, quality, cultural achievements of a nation, society (the state) determines the geopolitical position.